(untitled) (Journal of Applied Learning and Teaching, 2024)
This opinion piece explores the role of artificial intelligence in transforming the perception of errors into opportunities for personalized and lifelong learning. By leveraging AI’s ability to systematically analyze error patterns, educational institutions can create controlled environments where errors are embraced as catalysts for learning growth. The introductory section sets the context, presenting AI as a tool for shaping Education 4.0 and addressing urgent needs in the 21st century. The body of this opinion piece delves into its central claim: AI is the mechanism that will allow not only to take advantage of error but to intentionally and controllably encourage students to fail in learning as a starting point to turn errors into a catalyst for personalized learning. Claim-related arguments are provided, including using AI to analyze errors and nurture a growth mindset, preparing students for future challenges, and reducing teacher workloads. The conclusion emphasizes the significance of adopting an error-driven approach to foster lifelong learning. Overall, the paper underscores AI’s potential to revolutionize education by harnessing the power of errors.